Prevalence, clinical consequences and management of acute faecal incontinence with diarrhoea in the ICU: The FIRST™ Observational Study. (November 2015) - Binks, Rachel; De Luca, Enrico; Dierkes, Christine; Franci, Andrea; Herrero, Eva; Niederalt, Georg
There are limited data on the incidence and management of acute faecal incontinence with diarrhoea in the ICU. The FIRST™ Observational Study was undertaken to obtain data on clinical practices used in the ICU for the management of acute faecal incontinence with diarrhoea in Germany, UK, Spain and Italy. ICU-hospitalised patients ≥18 years of age experiencing a second episode of acute faecal incontinence with diarrhoea in 24 h were recruited, and management practices of acute faecal incontinence with diarrhoea were recorded for up to 15 days. A total of 372 patients had complete data sets; the mean duration of study was 6.8 days. At baseline, 40% of patients experienced mild or moderate-to-severe skin excoriation, which increased to 63% in patients with acute faecal incontinence with diarrhoea lasting >15 days. At baseline, 27% of patients presented with a pressure ulcer, which increased to 37%, 45% and 49% at days 5, 10 and 15, respectively. Traditional methods (pads, sheets and tubes) were more commonly used compared to faecal management systems during days 1–4 (76% vs. 47% faecal management system), while the use of a faecal management system increased to 56% at days 5–9 and 61% at days 10–15. At baseline, only 26% of nurses were satisfied with traditional management methods compared to 69% with faecal management systems. For patients still experiencing acute faecal incontinence with diarrhoea after 15 days, 82% of nurses using a faecal management systems to manage acute faecal incontinence with diarrhoea were satisfied or very satisfied, compared to 37% using traditional methods. These results highlight that acute faecal incontinence with diarrhoea remains an important healthcare challenge in ICUs in Europe; skin breakdown and pressure ulcers remain common complications in patients with acute faecal incontinence with diarrhoea in the ICU.